Quasi linear algorithm for modelling shoreline change from AIRSAR/POLSAR polarized data - Marghany, Maged; Hashim, Mazlan; Cracknell, Arthur P. (2007)
This paper presents a new approach for modeling shoreline change due to wave energy effects from remotely sensed data. The airborne AIRSAR and POLSAR data were employed to extract wave spectra information and integrate them with historical remotely sensed data such as aerial photography data to model the rate of change of the shoreline. A partial differential equation (PDF) of wave conversation model was applied to investigate the wave refraction patterns. The volume of sediment transport at several locations was estimated based on the wave refraction patterns. The shoreline change model developed was designed to cover a 14 km stretch of shoreline of Kuala Terengganu in peninsular Malaysia. The model utilized data from aerial photographs, AIRSAR, POLSAR and ERS-2 and in situ wave data. The results showed that the shoreline change rate modeled from the quasi-linear wave spectra model has a significant relationship with one modeled from historical vector layers of aerial photography, AIRSAR and POLSAR data. With the quasi-linear model an error of Â± 0.18 m/year in shoreline change rate determination was obtained with Cvv band. According to the above prospective, small polarized microwave sensor mounts on satellite platform might be provided similar out put results for shoreline change predictions. In fact, microwave spectra can be used with such tropical climate circumstances of cloud covers due to its longer wavelength and its polarization properties. As different polarization behaviour enable to study several coastal problems such as wave- current interaction, and wave-shoreline interaction.